2019
DOI: 10.1007/s10815-019-01658-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BRCA1 and BRCA2 mutations on ovarian reserve and fertility preservation outcomes in young women with breast cancer

Abstract: Purpose To determine the impact of BRCA1 and BRCA2 mutations on ovarian reserve and fertility preservation outcome. The main purpose and research question of the study is to determine the impact of BRCA1 and BRCA2 mutations on ovarian reserve and fertility preservation outcomes. Methods Prospective study: 67 breast cancer patients between 18 and 40 years old, undergoing a fertility preservation by means of oocyte storage were considered. Inclusions criteria for the study were age between 18 and 40 years old, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 35 publications
4
39
2
1
Order By: Relevance
“…They found that patients in the BRCA positive cohort, especially BRCA1 positive patients, needed a higher dose of gonadotropins, a longer duration of stimulation, and a statistically significant lower number of oocytes cryopreserved. 17 In conclusion, there is growing evidence indicating that BRCA mutations may be associated with decreased ovarian reserve and premature menopause, especially for BRCA1 mutation patients. Therefore, some authors suggest systematic fertility preservation in this population.…”
Section: Oocyte And/or Embryo Cryopreservationmentioning
confidence: 93%
See 2 more Smart Citations
“…They found that patients in the BRCA positive cohort, especially BRCA1 positive patients, needed a higher dose of gonadotropins, a longer duration of stimulation, and a statistically significant lower number of oocytes cryopreserved. 17 In conclusion, there is growing evidence indicating that BRCA mutations may be associated with decreased ovarian reserve and premature menopause, especially for BRCA1 mutation patients. Therefore, some authors suggest systematic fertility preservation in this population.…”
Section: Oocyte And/or Embryo Cryopreservationmentioning
confidence: 93%
“…In our search, 11 articles [17][18][19][20][21][22][23][24][25][26][27] considered anti-Mullerian hormone and antral follicular count as indexes of ovarian function in BRCA mutation carriers compared with wild-type controls (Table 1). In fact, anti-Müllerian hormone levels and antral follicular count are considered predictors of ovarian response during in vitro fertilization techniques, with lower levels suggestive of a poor response.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its function in mammalian meiosis was unclear, Brca1 mutant mice had impaired reproductive capacity and decreased primordial follicle counts ( Titus et al, 2013 ). Women with BRCA1 variations also presented with accelerated ovarian reserve decline ( Lin et al, 2017 ; Porcu et al, 2020 ). Therefore, BRCA1 was a potential causative gene of POI, which required comprehensive evaluation of somatic characteristics like BRCA2.…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“…Age is the most crucial factor swaying the success rate of FP: the efficacy of oocyte/embryo cryopreservation is strictly related to the number of mature oocytes retrieved, that is age-dependent, dropping precipitously after 35 years of age [ 53 , 54 ]. Moreover, the effectiveness of COS may be negatively impacted by BRCA status, considering the emerging evidence of a diminished ovarian reserve and a poor response to ovarian stimulation in BRCA1/2 -mutation carriers [ 55 , 56 ].…”
Section: Alternative Optionsmentioning
confidence: 99%